Eksplorasi Bakteri Selulolitik Dari Tanah Hutan Mangrove Baros, Kretek, Bantul, Yogyakarta - Nurrochman, Fajar; , Triastuti Rahayu, S.Si., M.Si (2015)
Cellulolytic bacteria are bacteria producing cellulase enzyme that functions to degrade cellulose. One of cellulolytic bacteria habitat is soil. This study aims to determine the population, the potential and characteristics of cellulolytic bacteria in mangrove forest land Baros, Kretek, Bantul, Yogyakarta. Sampling was done by the method of composite soil at a depth of 5, 10, 15 and 20 cm at five different points. Isolation of cellulolytic bacteria using selective media Carboxy Methyl Cellulose 1% (CMC 1%) with a spread plate method, incubated at 28 0C for 5 days. Cellulolytic bacterial isolates were grown colonies of each treatment was calculated and chosen different isolates of the overall treatment for isolated on NA medium. Characterization is done by growing the pure isolates were selected in CMC 1% media further congo red 0.1% drops to test the potential of cellulolitic (potential cellulolytic marked by the emergence of a clear zone around the colony). Results obtained 23 isolates of bacteria isolation of potentially degrade cellulose from 31 isolates. The population most commonly found at a depth of 20 cm (6,44x105 CFU/g), whereas at a depth of 5 cm there are at most a difference of character cellulolytic bacterial isolates (13 isolates) and most major cellulolytic activity index isolates possessed 3 is 6.38. Cellulolytic bacterial isolates obtained dominated by gram-negative cocci.